Lepra Hebraeorum: Ein antisemitisches Krankheitskonstrukt des 19. Jahrhunderts und seine Entwicklung - Jankrift, Kay Peter (Aschkenas, 2019)
In the first half of the 19th century, based on a misunderstanding and misinterpretation of biblical texts, several German physicians transformed the phenomenon named »Zara’at« in Hebrew into a specific disease called »Lepra Hebraeorum«, »Lepra Judeorum« or »Lepra Mosaica«. The authors applied traditional anti-Semitic stereotypes in order to explain the origins of this fictitious hereditary illness, which was said to befall Jews especially and to be transmitted by them to Non-Jewish populations. The genesis of »Lepra Hebraeorum« was completed by Christian ideas of the disease, linking leprosy to a sinful lifestyle and lust. However, in Jewish conceptions »Zara’at« never has been connected to sin or even to disease. It was rather regarded as a warning or punishment for derogatory speech. Soon after the discovery of »Mycobacterium leprae« in 1873 any reference to »Lepra Hebraeorum« disappeared from German medical writings.